Optimalisasi Konten Digital Instagram Sebagai Media Penyebaran Informasi PT TASPEN KC Bogor - Putra, Satria Sevan; Astuti, Vivien Febri (PRoMEDIA, 2025)
This study aims to analyze the Instagram content optimization strategy of PT TASPEN Bogor Branch Office (KC) as an institutional communication tool in conveying information about pension and social security programs. The study used a qualitative approach with a case study method. Data were collected through participatory observation during Field Work Practice (PKL) activities, in-depth interviews with account managers, and documentation and literature studies. The results showed that content optimization was carried out through upload consistency, improving visual quality, varying content formats, using calls to action, and branding consistency. These findings indicate that these strategies contribute to strengthening institutional credibility and meeting audience information needs. This study emphasizes the role of social media as a strategic communication instrument for public institutions, not just a means of publishing information.